Characterization of high quality carbon nanotubes synthesized via Aerosol -CVD (JOURNAL OF ADVANCES IN PHYSICS, 2015)
new Aerosol assisted CVD method of synthesizinglarge amount ofhigh quality carbon nanotubes (CNTs) with good structural parameters has been developed. We report the optimization of the process by experimental variables of thesynthesis condition. The effect of temperature in the hot zone of the reactor was investigated, and 840-950 0C was chosen as an optimum synthesis temperature. CNTs, obtained with different solvents as a carbon source have been analyzed, and ferrocene volume in cyclohexane solvent was varied, as the result of which has been grown MWCNTs with diameters of 10-85 nm and a small percent of SWCNTs with diameters of 0.85 and 1.14 nm. The position of Fe nanoparticles in the CNTs was defined by TEM observations, which show that Fe nanoparticles